2011
DOI: 10.2478/s11600-011-0063-8
|View full text |Cite
|
Sign up to set email alerts
|

On integrated sediment transport modelling for flash events in mountain environments

Abstract: A b s t r a c tSediment production and transport in mountain basins during shortterm, intense events depend on a variety of processes. Available models typically consider a limited portion of the phenomenological chain, frequently either sediment supply or solid transport along the waterways. On the other hand, proper depiction of on-site processes requires ability to model all the process stages and suitable integration between different models. In this manuscript, an integrated modelling is attempted for sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…The analysis of erosion phenomena deserves a separate mention, which may contribute to the creation of debris flow in rivers and hence they may result in sediment supply being involved in subsequent landslides [226] or debris flows [291]. Estimation of eroded volumes is not straightforward: in the literature, there are some empirical formulae aimed at furnishing the magnitude of the sediment supply, but the best approach is to quantify it by means of laser scanning and photogrammetry [121,122,129,204,235].…”
Section: Flowsmentioning
confidence: 99%
“…The analysis of erosion phenomena deserves a separate mention, which may contribute to the creation of debris flow in rivers and hence they may result in sediment supply being involved in subsequent landslides [226] or debris flows [291]. Estimation of eroded volumes is not straightforward: in the literature, there are some empirical formulae aimed at furnishing the magnitude of the sediment supply, but the best approach is to quantify it by means of laser scanning and photogrammetry [121,122,129,204,235].…”
Section: Flowsmentioning
confidence: 99%
“…Soil erosion has several on-site and off-site impacts on the environment: (1) loss of fertile soil with important consequences on agriculture [1]; (2) silting of reservoirs that reduces the storage capacity and interferes with dam operations [2][3][4]; (3) migration of pollution in which sediment transport is considered a means of transport for contaminants [5,6]; (4) increase of flood risk [7] and debris flow events [8]; and (5) geomorphic evolution of river beds [9] with possible impacts on the surrounding structures. At the basin scale, sediment production is the result of the complex interaction between different geomorphic processes: splash erosion, sheet erosion, rill erosion, gully erosion, bank erosion as well as mass movements [10].…”
Section: Introductionmentioning
confidence: 99%
“…Such a condition also favors the use of a single sediment size mimicking a granulometric distribution. Furthermore, the studies of [16,17,37] demonstrated (in the former case, for the same river considered here) that aggradation patterns in a downstream portion of a computational reach were almost independent of the sediment supply, provided that the duration of the modeled event was short. This piece of information was used to choose the extent of the computational domain, as already mentioned in Section 3.…”
Section: Model Parameterization/validationmentioning
confidence: 85%
“…These data were used as benchmarks for the simulation. In this way, an attempt was made to overcome the lack of field validation that is frequently a shortcoming in similar studies (e.g., [37,38]). …”
Section: Model Parameterization/validationmentioning
confidence: 99%